Review of Marine Pollution in Oil Spill Cases in terms of International Environmental Law - Damar Gymnastiar Ramdhani (LAFADZ JAYA Publisher, 2023)
This paper will focus on one of the cases related to pollution caused by the disposal of oil spills into the sea, a case study of the Exxon Valdez oil spill. In that matter, this paper can ''provide the stage'' for several relevant cases related to MARPOL 73/78 to build a discourse on environmental protection at sea based on the perspective of international environmental law. The writing of this paper uses a normative juridical legal research method. Judging from this Exxon Valdez case study, it can be agreed that this international treaty related to the prevention of pollution from ships or MARPOL has a renewal of its effectiveness if there has been an incident of pollution at sea in the past. The incident that impacted MARPOL 73/78 itself has also taught us the importance of protecting marine ecosystems.